Effect of Prenatal Vitamin D Supplementation on Placental Angiogenic Factors in Bangladesh (FS08-07-19). (13th June 2019) - Subramanian, Anita; Carr, Casey; Papp, Eszter; Murphy, Kellie; Mahmud, Abdullah Al; Roth, Daniel; Gernand, Alison
Abstract: Objectives: To determine the effect of prenatal vitamin D supplementation on expression of angiogenic factors in the placenta. Methods: This is a secondary analysis of the Maternal Vitamin D for Infant Growth trial, a randomized controlled trial of maternal vitamin D supplementation in Dhaka, Bangladesh. We examined the expression of angiogenic factors in placental tissues. Women ( n = 1300) were enrolled at 17–24 weeks gestation and randomized to receive: placebo, 4200 IU/week, 16, 800 IU/week or 28, 000 IU/week until delivery. We examined a subset of randomly selected placentas ( n = 80) collected at birth, which included 20 tissues (10 male & 10 female offspring) from each treatment group in maternal/fetal pairs. A full thickness placental core was collected; fixed in formalin and embedded in paraffin. Tissue sections were stained for vascular endothelial growth factor (VEGF) and placental growth factor (PlGF) using immunofluorescence. ImageJ was used to quantify intensity and % area of expression. T-tests were used to estimate the effects of each vitamin D dose on expression of angiogenic factors, compared to placebo. Interactions by fetal sex were also examined. Results: The mean (SD) for % area of expression was 17.0 (4.0) for VEGF and 14.8 (1.9) for PlGF. The mean (SD) for intensity was 6520 (1549) for VEGF and 5716 (734) for PlGF. There were no significant differences in VEGF and PlGF between any vitamin D treatment groups versus placebo for % area or intensity of expression (Table 1). The effect of vitamin D treatment was not modified by fetal sex. Conclusions: Vitamin D supplementation starting from mid-pregnancy until delivery did not effect expression of two key angiogenic factors in the placenta at term. The impact of periconception vitamin D supplementation on expression of angiogenic factors in the placenta remains unknown. Funding Sources: Bill and Melinda Gates Foundation. Supporting Tables, Images and/or Graphs: